Trichoscopy in pediatric age group - Subrata Malakar; Purva R Mehta; Samipa S Mukherjee (Wolters Kluwer Medknow Publications, 2018)
Approach to trichology in the pediatric age group is based on the clinical expertise of the dermatologist and investigative techniques. Currently, the trichoscope is an indispensible, noninvasive tool in the diagnosis of trichological disorders. It not only highlights the subtle tricoscopic points invisible to the naked eye but also serves as a prognostic and monitoring tool in therapeutic management. Trichoscopy goes a long way in improving the diagnostic and clinical acumen of the physician. In the pediatric age group, trichoscopy deals with pattern analysis ranging from hair shaft patterns to follicular, perifollicular, and interfollicular patterns. It not only describes the key trichoscopic features of noncicatricial alopecias, cicatricial alopecias, and genetic hair shaft defects but also helps to delineate various trichological mimics from each other. For compiling data, all trichology cases presenting to a tertiary care center were examined and photographed with a Fotofinder, DermLite Foto II Pro, and DermLite DL 3N. All trichological data were analyzed, and interpretations were based on the literature available.